2011
DOI: 10.3892/or.2011.1316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5,6-benzoflavone, indole-3-carbinol (I3C) and diindolylmethane (DIM) on chemically-induced mammary carcinogenesis: Is DIM a substitute for I3C?

Abstract: Abstract. the abilities of 5,6-benzoflavone (5,6-BF, a synthetic flavonoid), indole-3-carbinol (I3C, a plant derived product) or diindolylmethane (DIM, a condensation product of I3C) to alter the induction of mammary cancers induced by the carcinogens 7,12-dimethylbenzanthracene (DMBA) or N-methyl-N-nitrosourea (MNU) were evaluated. Interestingly, the first two agents act as aryl hydrocarbon receptor (AhR) agonists, while DIM does not. The agents were initially examined for their ability to inhibit DMBA-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
(29 reference statements)
1
13
0
1
Order By: Relevance
“…DIM, along with I3C were found to induce Nrf2-mediated phase II drug metabolizing (GSTm2, UGT1A1, and NQO1) and antioxidant (HO-1 and SOD1) genes and also shown synergism with isothiocyanates, such phenethyl isothiocyanate (PEITC) and sulforaphane (SFN) [82]. Lubet et al found that I3C acts as AhR agonist in mammary cancers while DIM does not, and DIM is not analogous to I3C in exerting their anticarcinogenesis effects [83]. DIM and I3C may act more effectively at earlier stage of prostate carcinogenesis and likely through a combination of effects on steroid hormones and/or xenobiotic metabolism pathway [84].…”
Section: Phytochemicals Used As Cancer Chemopreventive and Treatmementioning
confidence: 99%
“…DIM, along with I3C were found to induce Nrf2-mediated phase II drug metabolizing (GSTm2, UGT1A1, and NQO1) and antioxidant (HO-1 and SOD1) genes and also shown synergism with isothiocyanates, such phenethyl isothiocyanate (PEITC) and sulforaphane (SFN) [82]. Lubet et al found that I3C acts as AhR agonist in mammary cancers while DIM does not, and DIM is not analogous to I3C in exerting their anticarcinogenesis effects [83]. DIM and I3C may act more effectively at earlier stage of prostate carcinogenesis and likely through a combination of effects on steroid hormones and/or xenobiotic metabolism pathway [84].…”
Section: Phytochemicals Used As Cancer Chemopreventive and Treatmementioning
confidence: 99%
“…We showed that these genes were highly induced by the Ah receptor agonist 5,6-benzoflavone ). UAB30 clearly activated Ah receptor related genes (Table 4), and our prior findings showed that compounds that activate this receptor inhibit DMBA-induced mammary cancer and aflatoxin-induced liver cancer (Grubbs et al, 1995;Lubet et al, 2011). Therefore, we tested UAB30 (200 ppm) in the DMBAinduced mammary model, which reduced cancers by .80%, as much as a suboptimal dose (400 ppm) of 5,6 benzoflavone ( Fig.…”
Section: Tablementioning
confidence: 99%
“…This model examines the ability of an agent to block the initiation of mammary carcinogenesis (positive) in rats. We have published multiple articles using this model and recently showed that 5, 6 benzoflavone was highly effective (Grubbs et al, 1995;Lubet et al, 2011). In brief, female Sprague-Dawley rats were administered UAB30 (200 ppm), 5, 6 benzoflavone (400 ppm), or control diet from 43 days of age until 57 days of age.…”
Section: Effects Of Rxr Agonists On Gene Expressionmentioning
confidence: 99%
“…3.3), and glutathione, the most important protective non-protein thiol compound (Mugford et al 2011). Glucosinolates, mustard oil glycosides, represent one of the bioactive sulphur-containing secondary metabolites in plants, which occur almost only in members of order Brassicales Hamsa et al 2011;Lubet et al 2011;Malaguti et al 2011;Rajendran et al 2011;Razis et al 2011;Sharma et al 2011;Shimamoto et al 2011;Starrett and Blake 2011;Wiczk and Herman-Antosiewicz 2011). Their structure is based on ά-D-glucopyranose residue, which is linked via a sulphur atom to a (Z)-Nhydroximinosulphate ester.…”
Section: Connection Between Primary and Secondary Metabolism And Cadmmentioning
confidence: 99%